Potentially Inappropriate Medication and Associated Factors Among Older Patients with Chronic Coronary Syndrome at Hospital Discharge in Beijing, China - Zhao M (Dove Medical Press, 2021)
Mei Zhao,1,* Jun-Xian Song,2,* Fang-Fang Zheng,2 Lin Huang,1 Yu-Fei Feng1 1Department of Pharmacy, Peking University People’s Hospital, Beijing, People’s Republic of China; 2Department of Cardiology, Peking University People’s Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu-Fei FengDepartment of Pharmacy, Peking University People’s Hospital, No. 11 Xizhimen South Street, Xicheng District, Beijing, People’s Republic of ChinaTel +86-13611010053Email fengyufei@126.comPurpose: Medication therapy is crucial in the management of chronic coronary syndrome (CCS). The use of potentially inappropriate medications (PIMs) contributes to poor outcomes in older patients, making it a major public health concern. However, few studies are available on PIMs use in older Chinese CCS patients. To investigate the frequency of prescribed PIMs at discharge and explore risk factors in older adults with CCS.Patients and Methods: The cross-sectional study was conducted in a tertiary hospital in China over three months, from 1st October to 31st December, 2019. CCS patients aged over 60 years who were discharged alive were recruited. Information on demographics and medications at discharge was collected. Clinical data including diagnoses, frailty status, New York Heart Association (NYHA) class and age-adjusted Charlson Comorbidity Index (ACCI) were evaluated in each patient. PIMs were identified using the 2019 Beers criteria. Binary logistic regression was performed to recognize variables related to PIMs.Results: A total of 447 eligible patients with 2947 medications were included. The prevalence of PIMs use was 38%. Medications to be avoided, to be used with caution, and with drug–drug interactions were 38.4%, 48.9% and 12.7% of the PIMs, respectively. Medications with drug–disease/syndrome interactions and those adjusted for kidney function were not identified. The common PIMs were diuretics (37.1%), benzodiazepines and benzodiazepine receptor agonist hypnotics (15.2%), glimepiride (13.1%), and co-prescription of potassium-sparing diuretics and renin-angiotensin system (RAS) inhibitors (9.7%). Individuals with frailty syndrome, polypharmacy, multiple comorbidities, atrial fibrillation, psychiatric disorders and greater NYHA class severity were more likely to receive PIMs.Conclusion: Prescription of PIMs was a common burden in older adults. A CCS multidisciplinary team is needed to control PIMs, especially in vulnerable older patients.Keywords: potentially inappropriate medication, Beers criteria, chronic coronary syndrome, older adults, discharge